Evaluation of the CGIAR Research Program on Aquatic Agricultural Systems - Birner, Regina; Bhujel Ram; Rathgebe Eva M.; Sumberg James; Sriskandarajah Nadarajah; Sury Felix von (CGIAR Independent Evaluation Arrangement, 2015)
WorldFish is the Lead Center for the CGIAR Research Program on Aquatic Agricultural Systems (AAS), and the other CGIAR Center partners managing the program are the International Water Management Institute (IWMI) and Bioversity International. A number of development NGOs that work globally played a key role in AAS’s program design play a central role in its implementation.